2018
DOI: 10.30647/trj.v2i1.20
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Service Quality and Customer Satisfaction in Hotel Industry

Abstract: In the competitive hotel industry, individual hotels find ways to be unique to make their products and services shine amongst others. Hotels do not leave any stone unturned to deliver best of the services to magnetize the customers. Therefore, the purpose of this review paper is to study whether high level of quality service actually leads to satisfied customers and makes them loyal towards a particular hotel brand. Further, the study intends to explore whether SERVQUAL model is applicable for the hotels to sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
0
16
0
4
Order By: Relevance
“…The tourism and hospitality literature lays emphasis on the significance of the association between service quality and customer satisfaction [ 62 ]. The previous studies established the relevance of this relationship for hotels’ and restaurants’ success [ 63 , 64 ].…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…The tourism and hospitality literature lays emphasis on the significance of the association between service quality and customer satisfaction [ 62 ]. The previous studies established the relevance of this relationship for hotels’ and restaurants’ success [ 63 , 64 ].…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Hospitability industry exhibits a high interaction frequency with customers, the concept of quality refers to not only hotels' tangible products, but also service provided by hotels' staff as intangible element; it is a typical symbol impacting customer satisfaction (Stefano et al, 2015;Sharma and Srivastava, 2018;Shafiq et al, 2019). Fantastic service quality is more likely to positively contribute to customer satisfaction, especially among luxury hotels (Kucukusta et al, 2014;Mohamad et al, 2017;Tsang et al, 2015).…”
Section: Service Quality and Customer Satisfactionmentioning
confidence: 99%
“…The relevant reviewed literatures suggested that the SERVQUAL measurement model has been extensively adopted to recognise specific quality issues affecting customer satisfaction from five dimensions (empathy, responsibility, reliability, assurance and tangibility) (Sunil et al, 2018;Sharma and Srivastava, 2018;Shafiq et al, 2019;Jasinskas et al, 2016). In the meantime, due to the service-oriented feature exhibited by traditional luxury hotels, customers are frequently engaged with hotel employees, and the failures of service quality sometimes occur (Berezina et al, 2016;Cheng et al, 2019;Lewis and McCann, 2004;Wu et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Customers are the ultimate stakeholder. Hoteliers need to meet or exceed customer service expectations to satisfy customers and engender loyalty (Rather and Sharma, 2017; Sharma and Srivastava, 2018). COVID-19 has provoked new service provision customer expectations; hospitality businesses have been racing to provide both proactive and reactive innovations to accommodate the situation.…”
Section: Literature Reviewmentioning
confidence: 99%